Human interleukin-34-derived macrophages have increased resistance to HIV-1 infection. (November 2018) - Paquin-Proulx, Dominic; Greenspun, Benjamin C.; Kitchen, Shannon M.; Saraiva Raposo, Rui André; Nixon, Douglas F.; Grayfer, Leon
Highlights: Human macrophages differentiated by the M-CSF are susceptible to HIV-1. Macrophages differentiated by the IL-34 are much more resistant to HIV-1. The two populations express comparable surface levels of CD4 and CCR5. IL-34 macrophages express significantly greater levels of pertinent restriction factor genes. Abstract: The establishment of latent HIV-1 reservoirs in terminally differentiated cells represents a major impediment to the success of antiretroviral therapies. Notably, macrophages (Mϕs) are susceptible to HIV-1 infection and recent evidence suggests that they may be involved in long-term HIV-1 persistence. While the extensive functional heterogeneity seen across the Mϕ cell lineage parallels the spectrum of HIV-1 susceptibility reported across these cell subsets, the facets of Mϕ HIV-1 resistance and susceptibility remain to be fully defined. Notably, the differentiation of most Mϕ subsets depends on signaling through the macrophage colony-stimulating factor receptor (M-CSFR), which in addition to M-CSF, is now known to bind the unrelated interleukin-34 (IL-34) cytokine. The biological need for two M-CSFR ligands awaits full elucidation. Here, we report that Mϕs differentiated from human peripheral blood monocytes with IL-34 are substantially more resistant to HIV-1 infection than M-CSF-derived Mϕs. Moreover, while both Mϕ subsets express comparable surface protein levels of the HIV-1 receptor and co-receptor, CD4 and CCR5 respectively, the IL-34-Mϕs express significantly greater levels of pertinent restriction factor genes, potentially accounting for their greater resistance to HIV-1 infection than that observed in M-CSF-Mϕs. Together, our findings underline previously unexplored differentiation pathways resulting in HIV-1-susceptible and resistant Mϕ subsets and pave the way for further research that may overcome one of the last major hurdles in developing more successful antiretroviral therapy.